Epidemiology of survival pattern and its predictors among HIV positive patients on highly active antiretroviral therapy in Southern Ethiopia public health facilities: a retrospective cohort study - Abewa Kebede; Fasil Tessema; Gadisa Bekele; Zerihun Kura; Hailu Merga (AIDS Research and Therapy, 2020)
Abstract Background In resource poor countries like Ethiopia, little is known about the survival of patients treated with antiretroviral therapy which depends on different factors. Evidence shows that mortality has been high particularly in the first 3 to 6 months of initiating antiretroviral therapy. Hence, the study aimed to assess the Epidemiology of survival pattern and its determinants among adult HIV positive patients on highly active antiretroviral therapy. Methods Retrospective cohort study was employed among a total of 455 records of patients who were enrolled on antiretroviral therapy from September 2006 to August 2010. Socio-demographic, clinical, immunological, behavioral, and date of antiretroviral treatment initiation including date of follow up status were extracted. Significant predictor variables were identified by fitting Cox’s proportional hazard model using a backward stepwise method and statistical significance variables were declared based on a p-value less than 0.05. Results A total of 455 adult HIV/AIDS patients on ART contributed to 886.05-person-year of observation and 65.7% were alive and on treatment, 17.1% were lost to follow up and 7.5% died. The study showed that the estimated mortality was 4.4%, 5.3%, 6.1%, 7%, 7.5% and 7.5% at 6, 12, 24, 36, 48 and 60 months of follow up period, respectively. The overall incidence rate of mortality was 4.2 per 100 person-years of observation. In multivariate analysis age 45 and above (AHR: 3.72, 95% CI 1.21–11.4), bedridden functional status (AHR: 17.4, 95% CI 6.21–48.79), poor ART drug adherence (AHR: 4.52,95% CI 2.05–9.96), Tuberculosis co-infection (AHR: 4.1, 95% CI 1.84–9.13), non-disclosure (AHR: 4.9, 95% CI 1.82–12.89) and severe anemia (AHR: 5.1, 95% CI 1.81–14.21) were found predictors. Conclusion Patients with older age, tuberculosis infection, bedridden patients and severe anemia were predictors. Tracing poorly adhered patients and giving drug counseling as well as encouraging them for disclosure to their families is crucial to improve their survival.